Occipital nerve stimulation improves the quality of life in medically-intractable chronic cluster headache: Results of an observational prospective study. (October 2017) - Fontaine, Denys; Blond, Serge; Lucas, Christian; Regis, Jean; Donnet, Anne; Derrey, Stéphane; Guegan-Massardier, Evelyne; Jarraya, Bechir; Dang-Vu, Bich; Bourdain, Frederic; Valade, Dominique; Roos, Caroline; et al.
Background: Occipital nerve stimulation (ONS) has been proposed to treat chronic medically-intractable cluster headache (iCCH) in small series of cases without evaluation of its functional and emotional impacts. Methods: We report the multidimensional outcome of a large observational study of iCCH patients, treated by ONS within a nationwide multidisciplinary network (https://clinicaltrials.gov NCT01842763), with a one-year follow-up. Prospective evaluation was performed before surgery, then three and 12 months after. Results: One year after ONS, the attack frequency per week was decreased >30% in 64% and >50% in 59% of the 44 patients. Mean (Standard Deviation) weekly attack frequency decreased from 21.5 (16.3) to 10.7 (13.8) ( p = 0.0002). About 70% of the patients responded to ONS, 47.8% being excellent responders. Prophylactic treatments could be decreased in 40% of patients. Functional (HIT-6 and MIDAS scales) and emotional (HAD scale) impacts were significantly improved, as well as the health-related quality of life (EQ-5D). The mean (SD) EQ-5D visual analogic scale score increased from 35.2 (23.6) to 51.9 (25.7) ( p = 0.0037). Surgical minor complications were observed in 33% of the patients. Conclusion: ONS significantly reduced the attack frequency per week, as well as the functional and emotional headache impacts in iCCH patients, and dramatically improved the health-related quality of life of responders.